Curriculum Development Of Sexuality Education For Senior High School Student - Nurmansyah, Gupi Rohman; Haryono, Haryono; Kusumandari, Rafika Bayu (Universitas Negeri Semarang, 2021)
Adolescents are susceptible to many serious sexual problems in a growth period. The education sector has an obligation to give accurate information about sexuality for students. The purpose of this study to determine the implementation of sexual education curriculum in Semarang high school, develop a sexuality education curriculum, knowing validity and test its effectiveness. The methods is research and development (R & D) Borg and Gall design. Field studies and literature studies were carried out to get ideas as material for designing a sexuality education curriculum according to students' needs. Then the curriculum design is validated by experts. Testing of sexuality education curriculum products in the classroom to determine its effectiveness. Results: nothing comprehensif of sexuality education to implementation in learning. Validity of experts judges in the sexuality education of curriculum product is worth it for implementation in school. The study indicated that the students have increased understanding of sexuality knowledge. The students showed a change perception and good attitudes about the issue of sexuality after receiving this program. It was recommended as material for the government to make new policies. The teacher can be using a sexuality education curriculum to guide learning in class.